2016
DOI: 10.5348/ijcri-2016133-cr-10721
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral hydatid cyst: A rare cause of neurosurgical emergency

Abstract: International Journal of Case Reports and Images (IJCRI) is an international, peer reviewed, monthly, open access, online journal, publishing high-quality, articles in all areas of basic medical sciences and clinical specialties.Aim of IJCRI is to encourage the publication of new information by providing a platform for reporting of unique, unusual and rare cases which enhance understanding of disease process, its diagnosis, management and clinico-pathologic correlations. Hydatid cyst disease in childhood is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[6] Wani et al reported on 5 pediatric patients with supratentorial hydatid cyst aged between 8 and 13 years on whom they had performed emergency surgery because of neurological worsening. [7] Emergency surgery for intracranial hydatid cyst was reported in 7 cases in which it was supratentorial [7][8][9][10][11][12][13] and 2 in which it was infratentoria l [14,15] ( Table 1). These cases were notable because they consist of 7 pediatric and 2 adult patients; the present case was also an adult patient.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Wani et al reported on 5 pediatric patients with supratentorial hydatid cyst aged between 8 and 13 years on whom they had performed emergency surgery because of neurological worsening. [7] Emergency surgery for intracranial hydatid cyst was reported in 7 cases in which it was supratentorial [7][8][9][10][11][12][13] and 2 in which it was infratentoria l [14,15] ( Table 1). These cases were notable because they consist of 7 pediatric and 2 adult patients; the present case was also an adult patient.…”
Section: Discussionmentioning
confidence: 99%